Media Massa dan “Political Literacy”: Pemanfaatan Berita Politik di Kalangan Remaja - Suryadi, Karim Suryadi (FIkom Unisba, 2007)
The role of mass media in creating cognitive response concerning input function, conversion process, and political system output is lower than political system capability. This difference is due to two reasons: (1) in teenager’s thinking domain, input function, conversion process, and political output are more theoretical-abstract; (2) political news exposure in mass media is more highlighting demanded citizen characteristics as important attributes of political system capability. This means that though teenagers are considered to be important in political domain, political news exposure has not been considering teenagers’ psycho-political aspect.